Impact of caregiver burden in paediatric epilepsy at Charlotte Maxeke Johannesburg Academic Hospital, South Africa - Sabo, Umar Abba (My University, 2018)
Background: Chronic health conditions such as epilepsy may impose a high level of stress on the caregivers. The burden of epilepsy can cause significant dysfunction in the affected families resulting in a negative impact on the child’s adaptation to the disease. This study seeks to evaluate the effects of caregiver burden on the health-related quality of life (HRQOL) of the caregivers and their family functioning as well as factors associated with high impact of the caregiver burden. Methods: The participants consisted of primary caregivers who were involved in childcare for at least six months before study onset. Informed consent was obtained. One hundred and nine eligible caregivers recruited over a three months’ period completed questionnaires providing information on their socio-demographic and epilepsy-related variables as well as paediatric quality of life (PedsQL) family impact module. High impact on HRQOL/ Family functioning was defined by Score below the inter-quartile range. Results: The median HRQOL score of the caregivers was 46.3 (IQR = 31.3, 67.5) while the median family functioning score was 46.9 (IQR = 31.3, 71.9). In participants categorized with high impact, raw scores ≤ 31.3 were obtained for both caregiver burden and family functioning. The family functioning score correlated strongly with the HRQOL score of the caretakers, ρ = 0.78 and p<0.001. Multivariate analysis identified lower caregiver education level and a high seizure frequency as independent predictor of high impact of caregiver burden after adjusting for age of the caregivers and the number of anti-epileptic drugs taken. Conclusion: The burden of caregiving for children with epilepsy in Johannesburg impacts negatively on family functioning. The burden of care was associated with high seizure frequency and lower level of caregiver education.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Medicine Johannesburg, 2018.
Keywords: Epilepsy; Caregivers; Quality of Life; Pediatrics